Emergence of Academic Freedom in the American Academic and Legal Contexts; [Génesis de la Garantía de Libertad de Cátedra en el Contexto Académico y Jurídico Norteamericano] - Madrid-San Martin, M (Pontificia Universidad Catolica de Chile, 2022)
This paper presents the historical arguments that shaped the concept of academic freedom in the American context. The first cases on academic freedom are studied, whose main characteristic is that they were not presented before a court, but rather, they promoted academic debates. These arguments addressed the very notion of academic freedom, as well as the role played by universities and academic communities in the society. Because of this, this paper includes the opinions of actors directly involved in the most famous cases. Finally, this paper analyzes judicial cases, in which courts closely followed the arguments developed in academic debates. © 2022 Pontificia Universidad Catolica de Chile. All rights reserved.